Analisis IFE, EFE, dan balance scorecard pada grup perusahaan PT Kirana Megatara - Kusuma, Christian Chandra; Firdausy, Carunia Mulya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
This research objective aimed to analyze and evaluate the internal and external factors of the company and to design a Balanced Scorecard as an alternative to performance measurement tools to support the company’s vision, mission, and strategy to achieve competitive advantage. The internal and external factors are to know what are the strengths and weaknesses of the company, as well as the opportunities and threats from the outside of the company. Based on the SWOT analysis, PT Kirana Megatara can identify the key success factors to compete with other companies in the same industry. A Balanced Scorecard enables companies to record financial performance results as well as monitor progress in building the company’s ability and to obtain intangible assets that are required for future growth. Balanced Scorecard measures the performance of companies on the four perspectives of balance: financial, customer, internal business processes, and learning growth to create strategy maps of the company. Based on the Balanced Scorecard analysis, the current performance in PT Kirana Megatara is more focused on a financial perspective, which is the growth of the sales and profitability increment. To achieve long-term objectives, PT Kirana Megatara should also be concerned with the other three perspectives of the Balanced Scorecard.